Fluoxetine Attenuated Anxiety-Like Behaviors in Streptozotocin-Induced Diabetic Mice by Mitigating the Inflammation. (16th July 2019) - Yuan, Peng; Zhang, Jian; Li, Liang; Song, Zhendi
Abstract : Patients with diabetes mellitus (DM) showed an increased risk of anxiety. High anxiety levels are also shown to increase stress of diabetic patients, which may contribute to poor clinical outcomes. The mechanisms underlying the development of anxiety disorders in diabetic patients remain unknown. As a result, there are no available treatments yet. Here, we tested the hypothesis that glial cells in the hippocampal area of DM mice might be responsible for their anxiety-like behaviors. Furthermore, we postulated that treatment with antidepressant, fluoxetine, could reduce anxiety behaviors and prevent the dysregulation of glial cells (oligodendrocyte and astrocyte) in DM mice. Diabetic mice were administered a single injection of streptozotocin (STZ), followed by treatment with fluoxetine. Mice were then tested on Y maze, open field, dark and light transition, and elevated plus maze tests to measure the status of anxiety and cognition. After completing these behavioral tests, mice were sacrificed and western blot was used to detect the oligodendrocyte and astrocyte maker proteins in hippocampal tissues. Emphasis was directed towards adult oligodendrocyte precursor cells (OPCs) and their marker protein to measure their proliferation and differentiation. We found that fluoxetine could effectively mitigate the level of anxiety and attenuate the cognitive dysfunction in diabetic mice. Meanwhile, fluoxetine inhibited astrocyte activation in mice exposed to STZ, prevented the loss of myelin basic protein (MBP), and affected the function of OPCs in these diabetic mice. The results suggested that the changes of these glial cells in the brains of diabetic mice might be related to the high anxiety levels and cognitive deficit in DM mice. Fluoxetine could ameliorate the high anxiety level and prevent cognitive deficit via inhibiting astrocyte activation and repairing the oligodendrocyte damage.